Pelatihan Penulisan Abstrak dalam Karya Ilmiah pada Mahasiswa Prodi Farmasi S1 Universitas Bhamada Slawi - Fiqih Kartika Murti; Oktariani Pramiastuti; Desi Sri Rejeki (LPPM Universitas Bumigora, 2022)
The benefits of writing a scientific paper for college students are being able to develop the idea based on sources and build systemic mindset. One of the parts in the scientific paper is an abstract consisting of background, objective, method, result, conclusion, and key words; it can be written in Bahasa Indonesia and English. The abstract facilitates readers in understanding the contents of the scientific paper. Based on the result of questionnaire, the problems faced by the pharmacy students are that (1) 80% of them have never written an abstract; (2) 53% of them have not known the elements of abstract; and (3) 84% of them had difficulty in writing an English abstract. The public service aimed to provide knowledge and training on writing an abstract both Bahasa Indonesia and English for pharmacy students of University of Bhamada Slawi. By lecture, discussion, and practice, the results of public service showed that 95% of participants have known and written the elements of abstract in Bahasa Indonesia, 78% of participants could compose an abstract in Bahasa Indonesia and 71% of participants were able to write abstract in English.